Local Islamic Traditions and Adaptive Leadership: Arakan Sahur and Ulema Regeneration in Jambi - Ansori, Ansori; Setiawan, Heru; Fauzi, Hairul (SCAD Independent, 2025)
The declining regeneration of ulema presents a serious challenge to the sustainability of Islamic education in Jambi. This study investigates how the traditional Arakan Sahur ritual, once rooted in communal religious practice, has been reframed by Kiai into a leadership strategy to prepare future scholars. Emphasizing values of togetherness, discipline, social harmony, and empowerment, Arakan Sahur is adapted within pesantren to foster students’ spiritual resilience and leadership capacity. Employing a qualitative case study design, data were collected through interviews with Kiai, students, and community leaders, alongside observations of leadership practices reflecting Arakan Sahur values. Thematic analysis, strengthened by triangulation, revealed that these values underpin an adaptive leadership model that blends local wisdom with modern approaches, including digital da’wah tools. This adaptation strengthens the relevance of Islamic education, equipping students to navigate contemporary challenges while remaining rooted in tradition. The findings affirm the importance of preserving local religious practices as dynamic resources for leadership development in pesantren. Overall, the study shows how cultural traditions can be revitalized to support sustainable ulema regeneration and contribute to educational renewal in modern Islamic contexts.